2000
DOI: 10.1161/01.cir.101.21.2526
|View full text |Cite
|
Sign up to set email alerts
|

Coronary Nitric Oxide Production in Response to Exercise and Endothelium-Dependent Agonists

Abstract: Background —Endothelium-derived nitric oxide (NO) contributes to epicardial coronary artery vasodilation during exercise. However, blockade of NO production does not impair the increase in coronary blood flow (CBF) during exercise, suggesting that NO is not obligatory for exercise-induced coronary resistance vessel dilation. In contrast, the increases in CBF produced by endothelium-dependent agonists are decreased after NO blockade. Consequently, this study was performed to determine whether the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
1
4

Year Published

2003
2003
2017
2017

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 20 publications
2
25
1
4
Order By: Relevance
“…These findings coincide with ours, indicating that NO plays a pivotal role in the ACh-induced coronary vasodilation. Interestingly, they also noticed that a substantial number of animals they examined had negative arteriovenous NOx gradients between aorta and coronary sinus at rest (56). Recently, in vivo conversion of nitrite, which is the major pool of bioavailable NO, to NO has been proposed by enzymatic reduction with xanthine oxidoreductase, nonenzymatic disproportionation, or acidic reduction (57).…”
Section: Resultsmentioning
confidence: 99%
“…These findings coincide with ours, indicating that NO plays a pivotal role in the ACh-induced coronary vasodilation. Interestingly, they also noticed that a substantial number of animals they examined had negative arteriovenous NOx gradients between aorta and coronary sinus at rest (56). Recently, in vivo conversion of nitrite, which is the major pool of bioavailable NO, to NO has been proposed by enzymatic reduction with xanthine oxidoreductase, nonenzymatic disproportionation, or acidic reduction (57).…”
Section: Resultsmentioning
confidence: 99%
“…Studies have shown that regular physical activity promotes the reduction of the inactivation of nitric oxide (Fogarty et al, 2004;Traverse et al, 2000), increases the production of nitric oxide (Takamura et al, 2002), increases the expression of endothelial nitric oxide synthase (eNOS) (Griffin et al, 2001) and promotes angiogenesis induced by vascular endothelial growth factor, and, with the net effect of increasing the bioavailability of nitric oxide.…”
Section: Discussionmentioning
confidence: 99%
“…Propolis is a bee product (Apis mellifera L.) which presents in its composition mainly flavonoids and other compounds (Bankova et al, 2000;Marcucci et al, 2001), and has been used in folk medicine in many countries since ancient times, because it has antioxidant, antimicrobial and anti-inflammatory properties (Wang, 1993;Marcucci, 1995;Banskota et al, 2002). In this manner, the present study aimed to verify the effect of propolis alone and its association with swimming in dyslipidemia, left ventricular hypertrophy and atherogenesis of hypercholesterolemic mice that were receiving high-fat diet.…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations